Organisational Factors as Antecedents of University Academic Staff Research Productivity - Hiire, Geoffrey Boaz; Oonyu, Joseph; Kyaligonza, Robert; Onen, David (Journal of Education and Practice, 2020)
This study explored whetherorganisational factors such as technological progress, computer skills, research funding, and human resourceswere significant antecedents of academic staff research productivity in chartered private universities in Uganda. The study stemmed from reportedly low levels of research productivity of the academic staff in private universities in the country in spite of the numerousinterventionsby the Government of Uganda to spur research in both public and private higher education institutions.Using the quantitative approach anddescriptive cross-sectional survey research design, the researchers collected data using a pre-testedselfadministered questionnaire from a sample of 210 academic staff drawn from four out of nine chartered private universities in the country. The data were analysed with the use of appropriate descriptive and inferential statistical techniques. The study findings showed, among others, that while technological progress (β = 0.425, p = 0.000 < 0.05) and possession of computer skills (β = 0.329, p = 0.000 < 0.05) were positive and significant antecedents of research productivity, research funding (β = -0.003, p = 0.965 < 0.05)and human resources (β = 0.073, p = 0.186 < 0.05) were respectively negative and positive but non-significant antecedents of academic staff’s research productivity in the universities studied. Therefore, it was concluded that although organisational factors, overall, were significant antecedents of university academic staff’s research productivity, some of its elements such as technological progress and possession of computer skills were more significant antecedents than others – implying that in order to boost the research productivity of the academic staff, university managers need to place proportionate emphasis on these factors if they are to create an enabling research environment in their institutions.
Keywords: Organisational factors; Antecedents; Academic staff; Research productivity; Universities